2021
DOI: 10.3390/ijerph18052700
|View full text |Cite
|
Sign up to set email alerts
|

Safety-Specific Passive-Avoidant Leadership and Safety Compliance among Chinese Steel Workers: The Moderating Role of Safety Moral Belief and Organizational Size

Abstract: Despite the documented relationship between active-approaching leadership behaviors and workplace safety, few studies have addressed whether and when passive-avoidant leadership affects safety behavior. This study examined the relationship between two types of safety-specific passive-avoidant leadership, i.e., safety-specific leader reward omission (SLRO) and safety-specific leader punishment omission (SLPO), and safety compliance, as well as the moderating effects of an individual difference (safety moral bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…If the leader has good safety leadership, then most likely his employees are also good safety knowledge. In safety leadership, leaders must be responsible to their employees to have the necessary knowledge, confidence and awareness to do work safely and comfortably to reduce the risk of accidents in the workplace (Stiawan, 2024) Safety leadership is the responsibility of leaders in supporting the development of policies and practices that create safer societies (L. Liu et al, 2021) Therefore, leaders must have expertise in fostering a work safety culture within the company that is useful for the formation of active workers and initiatives to prioritize safety in every activity.…”
Section: Safety Leadership On Safety Knowledgementioning
confidence: 99%
“…If the leader has good safety leadership, then most likely his employees are also good safety knowledge. In safety leadership, leaders must be responsible to their employees to have the necessary knowledge, confidence and awareness to do work safely and comfortably to reduce the risk of accidents in the workplace (Stiawan, 2024) Safety leadership is the responsibility of leaders in supporting the development of policies and practices that create safer societies (L. Liu et al, 2021) Therefore, leaders must have expertise in fostering a work safety culture within the company that is useful for the formation of active workers and initiatives to prioritize safety in every activity.…”
Section: Safety Leadership On Safety Knowledgementioning
confidence: 99%
“… Jiang and Probst (2016) found that STFL strengthened SP whereas SPL weakened it. In a recent study from China, safety-specific passive-avoidant leadership negatively affects the safety compliance behavior, which is not conducive to the safety environment of enterprises ( Liu et al, 2021 ). Therefore, we similarly expected that:…”
Section: Theory and Hypothesesmentioning
confidence: 99%